Highly efficient flexible organic light-emitting devices based on PEDOT:PSS electrodes doped with highly conductive Pyronin B. (November 2019) - Kim, Dae Hun; Park, Na Hyun; Kim, Tae Whan
Abstract: Poly(3, 4-ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) is a promising material for utilization in flexible transparent electrodes. However, because the conductivity of PEDOT:PSS is as low as 1 S/cm or even lower, PEDOT:PSS has the inherent problem of a conductivity that is too low for it to be used in the fabrication of flexible, transparent electrodes for use in flexible organic light-emitting devices (OLEDs). Here, we report on hole injection enhancement in a highly conductive Pyronin-B-doped PEDOT:PSS electrode/hexaazatriphenylene hexacarbonitrile (HAT-CN) layer, a strong electron-accepting charge-generation layer, for use in highly efficient flexible OLEDs. While the conductivity of the pristine PEDOT:PSS is 1 S/cm, that of Pyronin-B-doped PEDOT:PSS is significantly increased to 1467 S/cm due to the dramatically enhanced screening effect for PEDOT:PSS films. The energy-band bending barrier at the interface between the Pyronin-B-doped PEDOT:PSS electrode and the HAT-CN layer is significantly decreased compared to that between the pristine PEDOT:PSS electrode and the HAT-CN layer, resulting in improved hole injection. The operating voltage and the current efficiency of the flexible OLEDs with Pyronin-B-doped PEDOT:PSS/HAT-CN electrodes (6.8 V, 26.03 cd/A) are similar to those of OLEDs with ITO/HAT-CN electrodes (7.7 V, 27.95 cd/A). The brightness of the OLEDs after 900 cycles of bending with a radius of curvature of 5 mm is 80% the initial brightness, indicative of the stability of these flexible devices under repeated bendings. Graphical abstract: Image 1 Highlights: Flexible organic light-emitting devices (OLEDs) were fabricated with the Pyronin-B-doped PEDOT:PSS electrode. Conductivity and sheet resistance of the Pyronin-B-doped PEDOT:PSS electrode were 1467 S/cm and 170.4 Ω/sq, respectively. The energy band bending at the interface between the Pyronin-B-doped PEDOT:PSS and the HAT-CN was significantly decreased. The maximum current efficiency for the OLEDs with Pyronin-B-doped PEDOT:PSS was 93.13% of that for the OLEDs with ITO. The brightness of the OLEDs with a bending radius of 5 mm after 900 cycles was 80% of the initial brightness.